Optimalisasi Transaksi Keuangan Menggunakan Zahir Accounting Versi 6.0 Pada Bengkel Rahmat Cimandala Raya Motor - Kurniasih, Rani; Wasiyanti, Sri; Utami, Lila Dini (PROFITABILITAS, 2025)
Manual accounting management remains a major challenge for small and medium-sized enterprises, including Bengkel Rahmat Cimandala Raya Motor. The lack of digitalized transaction recording often leads to delays in financial reporting, data inaccuracies, and difficulties in systematically preparing financial statements. This study aims to improve the efficiency of accounting processes through the implementation of Zahir Accounting version 6.0 software as a digital solution. The research employs a case study method using observation, interviews, and documentation techniques, conducted both before and after system implementation. The application of Zahir Accounting is expected to accelerate transaction recording, enhance the accuracy of financial reporting (such as journals, ledgers, balance sheets, and income statements), and facilitate overall financial monitoring. Therefore, the use of Zahir Accounting version 6.0 is anticipated to expedite managerial decision-making processes based on accurate data.